A novel mutation in the CRYAA gene associated with congenital cataract and microphthalmia in a Chinese family - Zixun Song; Nuo Si; Wei Xiao (BMC, 2018)
Abstract Background Congenital cataract is the leading cause of blindness in children worldwide. Approximately half of all congenital cataracts have a genetic basis. Protein aggregation is the single most important factor in cataract formation. Methods A four-generation Chinese family diagnosed with autosomal dominant congenital cataracts and microphthalmia was recruited at the Shengjing Hospital of China Medical University. Genomic DNA was extracted from the peripheral blood of the participants. All coding exons and flanking regions of seven candidate genes (CRYAA, CRYBA4, CRYBB2, CRYGC, GJA8, MAF, and PITX3) were amplified and sequenced. Restriction fragment length polymorphism (RFLP) assays were performed to confirm the candidate causative variant, c.35G > T in the CRYAA gene. We constructed pcDNA3.1(+)-CRYAA expression plasmids containing either the wild-type or the R12L mutant alleles and respectively transfected them into HEK293T cells and into HeLa cells. Western blotting was performed to determine protein expression levels and protein solubility. Immunofluorescence was performed to determine protein sub-cellular localization. Results A heterozygous variant c.35G > T was identified in exon 1 of CRYAA, which resulted in a substitution of arginine to leucine at codon 12 (p.R12L). The nucleotide substitution c.35G > T was co-segregated with the disease phenotype in the family. The mutant R12L-CRYAA in HEK293T cells showed a significant increase in the expression level of the CRYAA protein compared with the wild-type cells. Moreover, a large amount of the mutant protein aggregated in the precipitate where the wild-type protein was not detected. Immunofluorescence studies showed that the overexpressed mutant CRYAA in HeLa cells formed large cytoplasmic aggregates and aggresomes. Conclusions In summary, we described a case of human congenital cataract and microphthalmia caused by a novel mutation in the CRYAA gene, which substituted an arginine at position 12 in the N-terminal region of αA-crystallin. The molecular mechanisms that underlie the pathogenesis of human congenital cataract may be characterized by the prominent effects of the p.R12L mutation on αA-crystallin aggregation and solubility. Our study also expands the spectrum of known CRYAA mutations.